Technology, Pessimism, and Postmodernism
VII, 218 p.
Keywords: HOWARD P. SEGAL, FOR THE EDITORS In November 1979 the Humanities Department of the University of Michi gan's College of Engineering sponsored a symposium on ''Technology and Pessimism. " The symposium included scholars from a variety of fields and carefully balanced critics and defenders of modern technology, broadly defined. Although by this point it was hardly revolutionary to suggest that technology was no longer automatically equated with optimism and in turn with unceasing social advance, the idea of linking technology so explicitly with pessimism was bound to attract attention. Among others, John Noble Wilford, a New York Times science and technology correspondent, not only covered the symposium but also wrote about it at length in the Times the following week. As Wilford observed, "Whatever their disagreements, the participants agreed that a mood of pessimism is overtaking and may have already displaced the old optimistic view of history as a steady and cumulative expansion of human power, the idea of inevitable progress born in the Scientific and Industrial Rev olutions and dominant in the 19th century and for at least the first half of this century. " Such pessimism, he continued, "is fed by growing doubts about soci ety's ability to rein in the seemingly runaway forces of technology, though the participants conceded that in many instances technology was more the symbol than the substance of the problem.